Enhancing Facilitation Skills: Dancing with Dynamic Tensions. Issue 149 (March 2016) - Fierro, Rita Sinorita
Abstract: For evaluators there is a high price for bad facilitation: Without our knowing, we may favor our own priorities, forget participants' needs, submerge stakeholder voices, hide underlying causes, and undermine the impact of our work. The author shows how to improve one's facilitation skills by leveraging seven dynamic tensions: Hosting self and others, hosting present and absent stakeholders, observing group and individual dynamics, simplifying and unveiling complexity, listening and sensing emergence, using intuition and rational problem solving, and facing chaos and control.